Guess Destruction in the Child and Adolescent Humorous Tales of the 60's 90's Period - Mahdokht Poor Khaleghichatrodi; Alireza Sezavar; Maryam Jalali; Azam Estaji (Matn/Pizhūhī-i Adabī, 2020)
Satire, which is among the most important kinds of literature, has a long history in the world literature. The child and adolescent literature has always been a proper place to create satire because of the specific characteristics its target audience. A great number of critics and researchers have studied the satire and its different development methods. One of these theoirists was  Ivan Fonagy. His views on satire, especially in child and adolescent stories, are not well-known in Iran, but they are among the best theories of satire. Based on Ivan Fonagy's theory and by focusing on one of the most important components of his satire, "guess destruction", the present paper investigated some Iranian child stories which were written by the most famous writers of the contemporary era including Farhad Hassanzadeh, Shahram Shafiei, Ahmad Arablou, Sousan Taghdis and Saeid Hashemi. Ivan Fonagy's theory provided a specific definition of "guess destruction" and analyzed some children stories on that ground.